Interpretive regimes of violence in action: the “Welcome to Hell” demonstration during the G20 summit in Hamburg 2017 - Schattka, Chris (Public Order Policing, 2024)
The following chapter examines how violence occurred during the so-called “Welcome to Hell” demonstration, which took place during the 2017 G20 Summit in Hamburg. Violence during demonstrations is usually explained by building upon concepts, including mass, identity, and emotion. These concepts are each used to analyze unfolding events at demonstrations, but they vary in their inclusion and emphasis on reciprocal dynamics between police and crowd interpretations. It is proposed that an “interpretative regime” with an affinity for violence developed in the lead-up to the Hamburg demonstration, both among the police and the demonstrators, and this perspective contributed to the outbreak of violence. Interpretive regimes supporting violence are based on shared experiences. They arise when the parties involved accuse each other of intending to use violence, which justifies and increases the likelihood of their own violent behavior. During the “Welcome to Hell” demonstration, these interpretive regimes persisted until the day of the event and influenced how police and demonstrators interpreted the actions of each other during the demonstration.